Ice Ice Baby: Are Librarian Stereotypes Freezing Us out of Instruction? - Nicole Pagowsky (In the Library with the Lead Pipe, 2014)
In Brief: Why do librarians struggle so much with instruction? Part of the problem is that we have so many facets to consider: pedagogy, campus culture, relationships with faculty, and effectiveness with students. Research on student and faculty perceptions of librarians combined with sociological and psychological research on the magnitude of impression effects prompted us to […]